Biocontrol agents vis-Ã -vis fungicides in managing various diseases of tomato (Lycopersicon esculentum Mill.) in hills of Uttarakhand - S.N. SUSHIL; H.S. GUPTA, K.S. HOODA*, J.C. BHATT, D. JOSHI, (Indian Phytopathology, 2008)
Effect of various disease management tools on seed germination, seedling vigour, pre- and post–emergence rots, and foliar diseases of tomato (Lycopersicon esculentum Mill.) var. ‘Marglobe’ were studied as part of integrated disease management strategy under mid hill conditions of Uttarakhand. Five biocontrol agents viz., Trichoderma viride, Trichoderma harzianum, Pseudomonas fluorescens, mixture of T. harzianum and Pseudomonas fluorescens and Aspergillus niger along with two fungicides (thiram at nursery stage and mancozeb in transplanted crop) were applied as seed treatment (ST), nursery drenching (ND), seedling dip (SD) and foliar sprays (FS). All treatments showed significantly higher seedling emergence and vigour as compared to untreated check. Maximum mean seedling emergence (72.9, 63.0 & 62.9%) and vigour (1638, 1414 & 1474) were recorded in plots with treatment of thiram @ 0.2%, T. viride @ 0.4% and T. harzianum @ 1.0% as compared to 46.8 and 1099 in the check respectively. All the treatments significantly reduced preand post-emergence rots over check. In main crop, staking with removal of basal leaves 9" from the soil (SRBL) and SD in thiram solution (0.2%) with FS of mancozeb (0.2%) were found superior in managing early blight and buckeye rot over check. On the other hand four foliar sprays of bioagents had no effect on the incidence of these diseases. SRBL and SD in thiram solution with FS of mancozeb resulted in significantly higher yield of tomato over check.